Diversity and health strategies for newly resettled refugees. Issue 3 (29th June 2020) - Vikdahl, Linda; Ståhle, Göran; Gunnarsson, David; Saboonchi, Fredrik
Abstract : Purpose: In general, newly resettled refugees have poorer physical and mental health than native-born Swedes. This indicates that the society must make special efforts to enable refugees to attain health that is on a par with the rest of the population. The challenges rest primarily with employees in the public sector. But what resources do professionals need to meet the refugees' health needs? This paper is about the need to develop strategies for professionals working with diversity and health, with a focus on the establishment of newly resettled refugees in Sweden. Thus, the purpose of this paper is to identify the needs and obstacles in working with diversity and health for the newly resettled. Design/methodology/approach: The paper is based on focus group interviews with 40 professionals working in three large municipalities and one County Administrative Board, all of whom work with challenges related to migration and health on a daily basis. Findings: The needs expressed by the interviewees are primarily about developing and improving communications. Three important areas of communication were expressed: how information can be transferred from sender to receiver, institutionalization and interactions at different levels. Originality/value: This paper identifies important needs and obstacles when working with diversity and health in Sweden, with a focus on the establishment of newly resettled refugees. It is an important contribution because refugees in general have poorer physical and mental health than native-born Swedes and strategies to improve their health, therefore, need to be further developed.